2017
DOI: 10.15560/13.6.871
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the southern limit of Vampyrodes caraccioli Thomas, 1889 (Chiroptera, Phyllostomidae) and first record for Santa Catarina state, southern Brazil

Abstract: Three specimens of Vampyrodes caraccioli were collected in Corupá and São Bento do Sul, in Santa Catarina state, increasing its geographic distribution extension by 170 km south. These specimens also represent the first record for the species in Santa Catarina. The knowledge about bats in Santa Catarina has increased in recent years, showing the need of basic studies about richness and diversity in different regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(53 reference statements)
0
1
0
1
Order By: Relevance
“…After morphological, morphometric, and molecular analyses, Velazco and Simmons (2011) concluded that the two subspecies represented distinct species, of which only V. following characteristics: prominent white dorsal stripe and conspicuous white facial stripes, bicolored dorsal fur, tricolored ventral fur, presence of a fringe of hairs on the edge of the uropatagium, lingual cingula absent at the bases of the metacones of the upper molars, lack of M3, the presence of two cuspules on the posterior cristid of the second upper premolar, and lingual cingulid absent on the first lower molar Velazco and Simmons, 2011). Descriptions and measurements of V. caraccioli were provided by Husson (1954), Swanepoel and Genoways (1979), Lim et al (2005), Velazco et al (2010b), Simmons (2011), Carvalho et al (2014), Lopes et al (2016), andAlthoff et al (2017). No subspecies are currently recognized (Velazco and Simmons, 2011).…”
Section: Genus Sturnira Gray 1842mentioning
confidence: 99%
“…After morphological, morphometric, and molecular analyses, Velazco and Simmons (2011) concluded that the two subspecies represented distinct species, of which only V. following characteristics: prominent white dorsal stripe and conspicuous white facial stripes, bicolored dorsal fur, tricolored ventral fur, presence of a fringe of hairs on the edge of the uropatagium, lingual cingula absent at the bases of the metacones of the upper molars, lack of M3, the presence of two cuspules on the posterior cristid of the second upper premolar, and lingual cingulid absent on the first lower molar Velazco and Simmons, 2011). Descriptions and measurements of V. caraccioli were provided by Husson (1954), Swanepoel and Genoways (1979), Lim et al (2005), Velazco et al (2010b), Simmons (2011), Carvalho et al (2014), Lopes et al (2016), andAlthoff et al (2017). No subspecies are currently recognized (Velazco and Simmons, 2011).…”
Section: Genus Sturnira Gray 1842mentioning
confidence: 99%
“…O conhecimento sobre a distribuição e a história natural dos mamíferos de Santa Catarina vem aumentando desde as primeiras listas compilando as espécies documentadas para o estado (CIMARDI, 1996;CHEREM et al, 2004). Estudos conduzidos em diversas regiões do estado têm reportado uma mastofauna diversificada, atualmente estimada em 175 espécies, 144 das quais se referem a mamíferos terrestres (CHEREM et al, 2004;PASSOS et al, 2010;CARVALHO & FÁBIAN, 2011;REIS et al, 2011;DIAS et al, 2016;ALTHOFF et al, 2017ALTHOFF et al, , 2018CARVALHO et al, 2017;FEIJÓ et al, 2018;OLIVEIRA et al, 2021).…”
Section: Introductionunclassified